Implementasi Transisi PAUD ke SD melalui Pembelajaran yang Menyenangkan di SDN 2/X Parit Culum II - Nuri, Sukma; Sari, Tika (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
A This research aims to find out the implementation of the transition movement from PAUD to SD through fun learning at SDN 2/X Parit Culum II, along with the supporting and inhibiting factors in this transition. The research data are analyzed using qualitative techniques proposed by Miles and Huberman. The research subjects include the school principal, 1st-grade teachers, and 1st-grade students. Data for this research are obtained through interviews, observations, and documentation.The analysis results indicate that (1) the program of the PAUD to SD transition movement through fun learning at SDN 2/X Parit Culum II has been implemented comprehensively and runs smoothly. This is evidenced by the elimination of academic tests in the new student admission process, the application of a minimum 2-week school environment introduction period, and the implementation of learning by building six basic foundations for children; (2) Supporting factors in the implementation of the PAUD to SD transition movement through fun learning at SDN 2/X Parit Culum II include circulars regarding the strengthening of the PAUD to SD transition, teacher awareness that every child is entitled to basic foundational skills, and the background of students who have completed PAUD/TK. The inhibiting factors include teachers' misconceptions about academic performance and the presence of students who are not yet of sufficient age for elementary school.